Comparative evaluation of treatment of localized gingival recessions with coronally advanced flap using microsurgical and conventional techniques - Chandni Patel; Rupal Mehta; Surabhi Joshi; Tanvi Hirani; Chintan Joshi (Wolters Kluwer Medknow Publications, 2018)
Background: Coverage of gingival recession is a very precision-oriented procedure. Employment of operating microscope has proved to be a boon in various surgical procedures and therefore can have positive benefits on the outcome of a procedure. Aim: The aim of this study is to find out whether the use of an operating microscope in the surgical treatment of Millers Class I and Class II gingival recession defects could improve the outcome in terms of root coverage and final tissue appearance compared to those done by the conventional technique. Materials and Methods: This clinical study was carried out on ten patients with the presence of bilateral isolated gingival recession classified as Miller's Class I or Class II recession defect. The split-mouth design was used where coronally advanced flap with the placement of platelet-rich fibrin was done in defects in test (microsurgical) and control (conventional) groups. Various clinical parameters were recorded at baseline and then postoperatively at 3-months and 6-month intervals. Results: The visual analog scale scores showed a statistically significant difference between scores while all other parameters had no statistically significant difference in intergroup comparison after 3 and 6 months. Conclusion: While microscope permitted less traumatic and minimally invasive procedure, both groups showed convincing improvement in clinical parameters.